2015
DOI: 10.1016/j.vaccine.2015.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 testing of detoxified LPS/group B meningococcal outer membrane protein vaccine with and without synthetic CPG 7909 adjuvant for the prevention and treatment of sepsis

Abstract: Background Gram-negative bacteria (GNB) are a leading cause of nosocomial infection and sepsis. Increasing multi-antibiotic resistance has left clinicians with fewer therapeutic options. Antibodies to GNB lipopolysaccharide (LPS, or endotoxin) have reduced morbidity and mortality as a result of infection and are not subject to the resistance mechanisms deployed by bacteria against antibiotics. In this phase 1 study, we administered a vaccine that elicits antibodies against a highly conserved portion of LPS wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…CpG has demonstrated great promise in increasing seroprotective antibody titers in human clinical trials (18,19). However, the excessive inflammatory response induced by some vaccine formulations incorporating CpG sequences has increased the cost of its development and reduced the number of vaccines where it has been implemented (13,(17)(18)(19). Despite the promise of CpG, only one vaccine, HEPLISAV-B created by Dynavax Technologies, has achieved approval for use in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CpG has demonstrated great promise in increasing seroprotective antibody titers in human clinical trials (18,19). However, the excessive inflammatory response induced by some vaccine formulations incorporating CpG sequences has increased the cost of its development and reduced the number of vaccines where it has been implemented (13,(17)(18)(19). Despite the promise of CpG, only one vaccine, HEPLISAV-B created by Dynavax Technologies, has achieved approval for use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…CpG DNA also enables vaccines to be produced with less antigen (14), induces protective responses faster (15), and produces effective antitumor activity (16,17). CpG has demonstrated great promise in increasing seroprotective antibody titers in human clinical trials (18,19). However, the excessive inflammatory response induced by some vaccine formulations incorporating CpG sequences has increased the cost of its development and reduced the number of vaccines where it has been implemented (13,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Results trended toward sustained anti-LPS IgG and IgM responses after 180 but not 236 days. 49 However, the trial was underpowered due to recruitment ending prematurely.…”
Section: Review Of Prior Vaccination Attempts For Expecmentioning
confidence: 99%
“…In two separate Phase I studies, it has been shown to be safe, well tolerated, and immunogenic. 36 , 37 …”
Section: Introductionmentioning
confidence: 99%